2019
DOI: 10.1057/s41599-019-0268-z
|View full text |Cite
|
Sign up to set email alerts
|

‘I see you sharing, thus I share with you’: indirect reciprocity in toddlers but not infants

Abstract: Human societies are organised around cooperative interactions, the origins and development of which have become a timely topic. In this study, we investigated the development of indirect reciprocity in 18-24-month-old toddlers, and infants aged 6 months, on a two-phase sharing task with non-familiar individuals. In the first phase, we observed whether infants and toddlers differentiated and manifested a preference toward an individual altruistically sharing or acting selfishly. In the second phase, infants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In the absence of converging and independent evidence that this version of the game truly measures trust, a major concern is whether children's decisions were guided by generosity or altruistic motives rather than or in addition to a calculation of the risks associated with the investment. Indeed, prior work has shown that already during the preschool years, children tend to preferentially share resources with prosocial agents, engaging in acts of indirect reciprocity (e.g., Olson & Spelke, 2008; see also Nava et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of converging and independent evidence that this version of the game truly measures trust, a major concern is whether children's decisions were guided by generosity or altruistic motives rather than or in addition to a calculation of the risks associated with the investment. Indeed, prior work has shown that already during the preschool years, children tend to preferentially share resources with prosocial agents, engaging in acts of indirect reciprocity (e.g., Olson & Spelke, 2008; see also Nava et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocity in the business is defined as a reward from customers in return for sellers' or service providers’ exceptional services (Zulkifili and Yazid, 2020 ). According to Nava et al ( 2019 ), cooperative interaction such as reciprocity naturally develops at a very early age and our society is organized around this interaction. Thus, in the business world, positive reciprocity usually brings a positive influence on businesses’ growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The origin of indirect reciprocity has also been studied in social psychology. A field study investigated the development of indirect reciprocity in 18-24-month-old toddlers and in infants aged around six months [145]. The results showed that toddlers reciprocated prosocial behavior indirectly.…”
Section: Indirect Reciprocity In Various Disciplinesmentioning
confidence: 99%